PURCHASING DECISION OF RESIDENTIAL PROPERTY IN CITRALAND SURABAYA: EVIDENCE FROM INDONESIA - Sonata Christian; Yusravhika P. Adhianti (International Journal of Accounting, Finance and Business, 2020)
This study aims to determine the effect of advertising, online marketing and event on purchasing residential property in CitraLand Surabaya, Indonesia. CitraLand Surabaya is an integrated residential property over 2500 hectares in West Surabaya that is highly sought after by upper class families in Indonesia. This study is a quantitative research with questionnaire as primary data collection method and using multiple linear regressions for data analysis. The population in this study were 4.156 families who have purchased residential properties in CitraLand Surabaya. Based on multiple regression analysis shows that purchasing decision equation are Y = 2,048 +0,187X1 + 0,069X2 + 0,3062X3. The result of this study reveals that the effect of advertising, online marketing and event variables only 36,9% toward purchasing residential property in CitraLand Surabaya. The other findings of this study that only advertising (X1) and Event (X3) have significance individual influence toward purchasing decision.